Clinical Profiles and Outcomes of Heart Failure in Five African Countries: Results from INTER-CHF Study. Issue 1 (30th July 2021) - Karaye, Kamilu M.; Dokainish, Hisham; ElSayed, Ahmed; Mondo, Charles; Damasceno, Albertino; Sliwa, Karen; Balasubramanian, Kumar; Grinvalds, Alex; Yusuf, Salim; ,
Background: A wide knowledge gap exists on the clinical profiles and outcomes of heart failure (HF) in sub-Saharan Africa. Objectives: To determine the clinical profiles and outcomes of HF patients from five African countries. Methods: The INTERnational Congestive Heart Failure Study (INTER-CHF) is a prospective, multicenter cohort study. A total of 1, 294 HF patients were consecutively recruited from Nigeria (383 patients), South Africa (169 patients), Sudan (501 patients), Uganda (151patients), and Mozambique (90 patients). HF was defined according to the Boston criteria for diagnosis. Cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) score. Results: Of the 1294 patients, 51.4% were recruited as out-patients, 53.7% had HF with reduced ejection fraction (EF), 30.1% had HF with mid-range EF and 16.2% had HF with preserved EF (16.2%). The commonest etiologies of HF were hypertensive heart disease (35%) and ischemic heart disease (20%). The mean MoCA score was highest in Uganda (24.3 ± 1.1) and lowest in Sudan (13.6 ± 0.3). Prescriptions for guideline-recommended HF therapies were poor; only 1.2% of South African patients received an Implantable Cardioverter Defibrillator, and none of the patients received Cardiac Resynchronised Therapy. The composite outcome of death or HF hospitalization at one year among the patients was highest in Sudan (59.7%) and lowest in Mozambique (21.1%). Six variables were associated with higher mortality risk, while digoxin use (adjusted hazard ratio [aHR]: 0.69; 95% confidence interval [CI]: 0.49–0.97; p = 0.034) and 10mmHg unit increase in systolic blood pressure (aHR 0.86; 95%CI 0.81–0.93; p < 0.001) were associated with lower risk for mortality. Conclusions: This is the largest HF study in Africa that included in- and out-patients from the West, East, North, Central and South African sub-regions. Clinically relevant differences, including cognitive functional impairment, were found between the involved countries.